L1 Transfer: Indonesian Grammatical Interference (IGI) on pre-Service English Teachers’ L2 Writing - zelly putriani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
It is recognized that second and foreign language (L2) learners’ production is influenced by their first language (L1). Pre-service English teachers, who are assumed to have good English language proficiency, also demonstrate influences from their L1 (Indonesian) in relation to English grammar production. Through an explanatory case study, I conducted a writing for translation test which asked the study participants to identify 21 grammatical differences between English and Indonesian. The test was designed to reveal the dominant types of Indonesian grammatical interferences made by pre-service English teachers. The aim of the study was to provide empirical evidence to support these findings, and to consider their implications for pre-service English teachers and education practitioners more broadly. Through both error analysis and interference analysis, I found 805 Indonesian grammatical interference cases, categorized into 20 types of Indonesian interference. Following this fact, six dominant types of interferences were established (adjective and adverb, to be, active and passive, number, tense, and question form). The findings indicate that, because of Indonesian L1 transfer, pre-service English teachers had failed to adequately master these six parts of fundamental English grammar. Thus, meaning and form transfers from their L1 were impacting on the participants’ use of English grammar. The results have implications for English teaching pedagogy, and in particular for pre-service English teachers’ awareness of Indonesian grammatical interference (IGI).